Labor potential of innovative economy: problem statement (Путеводитель предпринимателя, 2020)
In the article is analyzed the essence of human capital, labour potential, is considered their relationship. The conclusion is made that the labour potential is a decisive factor in the achievement of strategic goals of the company, formation of innovation economy. One of the main obstacles innovative development of the economy is the inadequacy of the existing institutional structure of the opportunities of its development, the existence of gap between available human capital and the effectiveness of the implementation of the labor potential.